WORKSHOP PEMBELAJARAN BIODIVERSITAS PADA MGMP BIOLOGI SMA DI KABUPATEN LAMPUNG BARAT KAWASAN TAMAN NASIONAL BUKIT BARISAN SELATAN - Arwin Surbakti; Tina Yunarti; Santy Setiawati; Tia Agnesa (Universitas Lampung, 2022)
The results of the biodiversity learning of class X high school students in heritage locations contained some material that was not yet optimal. The existence of heritage students still does not understand related to the material, its role, and its protection. The existence of heritage in BBSNP in learning has not been linked contextually. MGMP in the field of biology accommodates the problem of learning biology, but MGMP activities in the district are still not optimal. It also has not utilized MITRA for the preparation of learning. The Ministry of Forestry is a very important partner in terms of biodiversity material and this material must be adopted in learning by the challenges of the current state of critical biodiversity. The MGMP workshop in the field of biology in partnership with the Ministry of Forestry is endeavored to produce Lesson Plan products and in-depth materials related to biodiversity which were developed through FGDs to be carried out in high schools in West Lampung Regency, heritage locations. The results of the activity were carried out in Kubu Perahu and were attended by 15 biology teachers and also 3 resource persons from TNBBS. Submission of research results from resource persons related to student knowledge about biodiversity for West Lampung, followed by biodiversity hertitage from BBSNP, followed by discussion in the framework of a workshop. reliable for changing the paradigm of students on the importance of the existence of biodiversity to be conserved in the heritage area.Keywords: biodiversity; learning; bukit barisan selatan national parkAbstrakHasil pembelajar biodiversitas siswa SMA kelas X di lokasi heritage terdapat beberapa materi belum optimum. Keberadaan heritage siswa masih banyak belum mengerti terkait dengan materi, peranan dan perlindungannya. Keberadaan heritage di TNBBS pada pembelajaran belum dikaitkan secara kontekstual. MGMP bidang biologi mewadahi permasalahan pembelajaran biologi akan tetapi kegiatan MGMP di kabupaten masih belum optimum. Hal ini juga belum memanfaatkan MITRA untuk pembuatan persiapan pembelajaran. Departemen Kehutanan merupakan mitra yang sangat penting terkait materi biodiversitas dan materi ini wajib diadopsi dalam pembelajaran sesuai dengan tantangan terdapat keadaan biodiversitas kritis pada saat ini. Workshop MGMP bidang biologi bermitra dengan Departemen Kehutanan diupayakan menghasilkan produk Rencana Pembelajaran dan materi mendalam terkait biodiversitas yang dikembangkan melalui FGD untuk dilakukan di SMA pada Kabupaten Lampung Barat lokasi heritage. Hasil kegiatan dilaksanakan di Kubu Perahu dan di hadiri guru biologi sebanyak 15 guru dan juga 3 nara sumber dari TNBBS. Penyampaian hail penelitian dari nara sumber terkait pengetahuan siswa tentang biodiversitas untuk Lampung Barat dilanjutkan dengan hertitage biodiversitas dari pihak TNBBS dilanjutkan dengan diskusi dalam rangka workshop. yang handal untuk mengubah paradigma siswa pentingnya keberadaan biodiversitas untuk dikonservasi dalam kawasan heritage. DOI: https://doi.org/10.23960/rp/v2i1.hal.76-80